2023
DOI: 10.1037/pha0000585
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management for smokers with mental health disorders and smoking-sensitive conditions caused or exacerbated by tobacco use: A review of existing studies, intervention parameters, and research priorities.

Abstract: Cigarette smoking is highly prevalent in people with smoking-sensitive conditions and mental health disorders. As early as the 1960s, evidence indicated the efficacy of contingency management (CM) for smoking cessation in various populations. This invited review is a critical appraisal of existing CM studies on smoking cessation in populations presenting smoking-sensitive conditions. It is particularly focused on examining the differences between two populations: smokers presenting health-related conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Contingency management (CM) for smoking cessation (i.e., using financial incentives to reinforce biochemically verified smoking abstinence) may be a promising intervention for patients with CVD who smoke as it can be delivered by nonclinical staff and may help alleviate the need for clinicians to comprehensively address smoking cessation with their patients. Controlled studies have demonstrated that CM effectively promotes smoking abstinence in medically vulnerable populations such as pregnant women, patients with chronic obstructive pulmonary disease (COPD), and patients with comorbid psychiatric conditions and other substance use disorders (Bolívar et al, 2021; González-Roz & Secades-Villa, 2022; Secades-Villa et al, 2020; Streck et al, 2018; Tidey et al, 2011; Wilson et al, 2018). We know of no published research examining CM for smoking cessation in patients with or at risk for developing CVD; thus, clinical trials examining the efficacy of CM for smoking cessation in this patient population are sorely needed (Barth et al, 2015; Prochaska & Benowitz, 2015; Suissa et al, 2017).…”
mentioning
confidence: 99%
“…Contingency management (CM) for smoking cessation (i.e., using financial incentives to reinforce biochemically verified smoking abstinence) may be a promising intervention for patients with CVD who smoke as it can be delivered by nonclinical staff and may help alleviate the need for clinicians to comprehensively address smoking cessation with their patients. Controlled studies have demonstrated that CM effectively promotes smoking abstinence in medically vulnerable populations such as pregnant women, patients with chronic obstructive pulmonary disease (COPD), and patients with comorbid psychiatric conditions and other substance use disorders (Bolívar et al, 2021; González-Roz & Secades-Villa, 2022; Secades-Villa et al, 2020; Streck et al, 2018; Tidey et al, 2011; Wilson et al, 2018). We know of no published research examining CM for smoking cessation in patients with or at risk for developing CVD; thus, clinical trials examining the efficacy of CM for smoking cessation in this patient population are sorely needed (Barth et al, 2015; Prochaska & Benowitz, 2015; Suissa et al, 2017).…”
mentioning
confidence: 99%